2006
DOI: 10.1002/ajpa.20502
|View full text |Cite
|
Sign up to set email alerts
|

An elusive paleodemography? A comparison of two methods for estimating the adult age distribution of deaths at late Classic Copan, Honduras

Abstract: Comparison of different adult age estimation methods on the same skeletal sample with unknown ages could forward paleodemographic inference, while researchers sort out various controversies. The original aging method for the auricular surface (Lovejoy et al., 1985a) assigned an age estimation based on several separate characteristics. Researchers have found this original method hard to apply. It is usually forgotten that before assigning an age, there was a seriation, an ordering of all available individuals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 21 publications
0
39
0
1
Order By: Relevance
“…Bayesian approaches allow prior probabilities of age to be incorporated into models, allowing for more nuanced investigation of past populations and comparison of mortality profiles (e.g. Gowland and Chamberlain 2005;Nagaoka and Hirata 2008;Redfern and Chamberlain 2011;Storey 2007). The same approach can be used for individual age estimates (Boldsen et al 2002).…”
Section: Age Ranges and Probability Densitiesmentioning
confidence: 99%
“…Bayesian approaches allow prior probabilities of age to be incorporated into models, allowing for more nuanced investigation of past populations and comparison of mortality profiles (e.g. Gowland and Chamberlain 2005;Nagaoka and Hirata 2008;Redfern and Chamberlain 2011;Storey 2007). The same approach can be used for individual age estimates (Boldsen et al 2002).…”
Section: Age Ranges and Probability Densitiesmentioning
confidence: 99%
“…Age estimation methods do not produce specific point estimates of estimated age, but rather, estimated intervals of age (e.g., [45][46][47][48][49][50][51][52][53][54][55]. Thus, the extreme of the age range nearest to the chronological age was used to calculate the bias and the absolute error of the estimation.…”
Section: Methodsmentioning
confidence: 99%
“…In a number of applications it is shown that if an appropriate prior age-at-death distribution is used, then the method will provide accurate "coverages". Recent work in this field points to Bayesian inference-based methods, the utility and efficacy of which have already been demonstrated (Godde and Hens, 2012;Lucy et al, 1996;Rissech et al, 2006Rissech et al, , 2007Storey, 2007).…”
Section: Implications For the Mortality Profilesmentioning
confidence: 99%